Thyroid scintigraphy of healthy cats using small-field-of-view gamma cameras - Cha, Sijin; Chae, Yeon; Yun, Taesik; Kim, Hakhyun; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2024)
IntroductionSmall-field-of-view (SFOV) gamma cameras can offer higher sensitivities than conventional gamma cameras. However, there are currently no reports on the efficacy and safety of thyroid scintigraphy using SFOV gamma cameras in veterinary medicine. Therefore, we aimed to evaluate the efficacy and radiation safety of an SFOV gamma camera for feline thyroid scintigraphy.Materials and methodsThree veterinary staff members (operator, staff 1, and staff 2) performed thyroid scintigraphy on 10 healthy cats in this study. The operator administered either 2 or 4 mCi of technetium-99m pertechnetate (99mTcO−4) through the cephalic vein. At 20, 40, and 60 min after injection, thyroid images were obtained using a SFOV gamma camera under various acquisition conditions (100,000, 150,000, and 200,000 counts and 30 and 60 s). Thyroid scintigraphy images were analyzed by calculating the thyroid-to-salivary ratios (TSR) and thyroid-to-background ratios (TBR). Surface and ambient radiation were measured hourly from immediately after injection to 6 h. The cumulative occupational radiation doses were measured during the procedure.ResultsThe TSR and TBR median values aligned with the previously reported normal range obtained using a large-field-of-view gamma camera. There were no notable differences in TSR and TBR between the two doses of 99mTcO−4, nor across acquisition conditions and timelines. The 4-mCi group consistently emitted more ambient (p < 0.05) and surface (p < 0.05) radiation than did the 2-mCi group. Staff 1 consistently received higher cumulative radiation doses than did staff 2 and the operator (p < 0.05).ConclusionThe SFOV gamma camera demonstrated adequate image quality for thyroid scintigraphy in healthy cats even with relatively low doses and short acquisition conditions. Radiation exposure during the procedure posed minimal safety concerns. Therefore, the SFOV gamma camera could be a valuable tool for evaluating thyroid glands in cats.